Effects of morinda citrifolia (noni) and diet complexity on growth performance in weanling pigs - Feoli, C.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to determine the effects of concentration (0, 0.75, 1.5, 3.0, and 6.0%) of Morinda citrifolia (no-ni; Morinda Agricultural Products, Orem, UT) and diet complexity in weanling pigs. In Exp. 1, 210 pigs (initially 13.4 lb) were used in a 35-d growth assay; there were 7 pigs per pen and 6 pens per treatment. Diets were corn-soybean meal-based, and lysine concentrations were 1.8% for d 0 to 7, 1.6% for d 7 to 21, and 1.4% for d 21 to 35 with feed and water con-sumed on an ad libitum basis. Increasing the concentration of noni in the diet from 0 to 3% had no effects on pellet durability index (PDI) for the d 0 to 7 and 7 to 21 diets. Average daily gain (quadratic effect, P < 0.03) and F/G (quadratic effect, P < 0.10) for d 0 to 7 and F/G for d 0 to 21 (quadratic effect, P < 0.04) improved as noni concentration in the diet was increased from 0 to 0.75%. However, no treatment effects were observed overall (d 0 to 35). For Exp. 2, 168 pigs (initially 13.9 lb) were used in a 35-d growth assay; there were 6 pigs per pen and 7 pens per treatment. Treatments were arranged as a 2 × 2 factorial with main effects of diet formulation (simple vs. complex) and noni addition (0 vs. 3%). Simple diets had the same minimum nutrient specifications as complex diets but had no added lactose or spray-dried animal plasma for d 0 to 7 and only 10% added whey for d 7 to 21. Pelleting data indicated improved PDI with no additional energy inputs when noni was added to the simple diets (for d 21 to 35). Pigs fed simple diets had lower ADG (P < 0.06) for d 0 to 7 and lower ADG and ADFI (P < 0.06) for d 0 to 21 than pigs fed complex diets. During d 0 to 35 for ADG and d 0 to 21 for F/G, addition of noni to the simple diets had negative effects (diet complexity × noni interaction, P < 0.02). In conclusion, adding 0.75 to 3% noni to complex diets improved growth performance early in a titration experiment but had negative effects when added to the simple diet formulations used in a second experiment.
Keywords: Diet complexity; Dose titration; Morinda citrifolia; noni